1st Annual Conference of Midwifery 2020
DOI: 10.2478/9788366675087-008
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Sources of Information and Social Culture with the Immunization of Measles Rubela (MR) in Lubuk Buaya Primary Health Center Padang City

Abstract: Measles Rubella (MR) immunization is a way to actively increase a person's immunity against antigens (measles and rubella viruses), so that if later exposed to similar antigens, measles and rubella infection will not occur. The purpose of this study was to determine the association of information and socio-cultural sources with the administration of Measles Rubella (MR) immunization in children aged 9 months to 5 years in the working area of Lubuk Buaya Health Center, Padang City. This study was a quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…This is consistent with the study's findings, which indicate that respondents with secondary to postsecondary education had a similar proportion of respondents who routinely performed ANC (Ningsih, 2020). Another study showed that age, knowledge, attitudes, work, and family support are related factors influencing the frequency of antenatal care visits (Oktova, Halida, & Rusmat, 2023). Work is another aspect; according to (Fatmawati et al, 2022) research, moms who work will have less time to monitor their pregnancy, which indirectly limits their chance to gain more insight and knowledge because they work longer hours.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with the study's findings, which indicate that respondents with secondary to postsecondary education had a similar proportion of respondents who routinely performed ANC (Ningsih, 2020). Another study showed that age, knowledge, attitudes, work, and family support are related factors influencing the frequency of antenatal care visits (Oktova, Halida, & Rusmat, 2023). Work is another aspect; according to (Fatmawati et al, 2022) research, moms who work will have less time to monitor their pregnancy, which indirectly limits their chance to gain more insight and knowledge because they work longer hours.…”
Section: Discussionsupporting
confidence: 90%